Complex Regional Pain Syndrome: Thalamic GMV Atrophy and Associations of Lower GMV With Clinical and Sensorimotor Performance Data - Domin, Martin; Strauss, Sebastian; McAuley, James H.; Lotze, Martin (Frontiers in Neurology, 2021)
Results on grey matter alterations in complex regional pain syndrome (CRPS) showed heterogeneous findings. Since CRPS is a rare disease, most studies included only small and heterogeneous samples resulting in a low reliability of findings between studies. We investigated 24 CRPS patients with right upper limb affection in the chronic stage of disease using structural MRI and clinical testing. We focused on grey matter volume (GMV) alterations of the brain in comparison to 33 age matched healthy controls, their association to clinical characteristics (duration of pain syndrome and pain intensity ratings) and sensorimotor performance (finger dexterity and spatiotactile resolution). When applying an explorative whole brain analysis CRPS patients showed lower GMV in the bilateral medial thalamus. No other areas showed a relevant GMV difference for the group comparisons. When applying a region of interest driven approach using anatomical masks of the thalamus, ACC/mPFC, putamen and insula we found relevant associations of clinical and behavioral data in ACC and insula. Whereas the GMV in ACC showed negative associations with pain intensity and CRPS duration, the GMV of the left posterior insula was negatively associated with sensorimotor performance of the affected hand side. Overall, our results are in accordance to results of others describing a thalamic reduction of GMV in patients with neuropathic pain and are also in accordance with associations of pain intensity and duration with reduced ACC in general in patients with chronic pain syndromes. Sensorimotor performance seems to be related to posterior insula GMV reduction, which has not been described yet for other patient groups.